Causal Relationship among Foreign Reserves, Exchange Rate and Foreign Direct Investment: Evidence From Nigeria - Osigwe, Augustine C.; Uzonwanne, Maria Chinecherem (International Journal of Economics and Financial Issues, 2015)
This study scrutinized the Granger causality of foreign reserves, exchange rate and foreign direct investment in Nigeria. The results of the ADF and PP unit root test for stationary of the variables showed that all the variables were non-stationary at levels, but become stationary after first differences. The Johansen co-integration test revealed long run relationship among the variables. The results of the Granger causality test indicated unidirectional causality from exchange rate to foreign reserves. Consistently from lag one to lag two; unidirectional causality existed from foreign direct investment to foreign reserves. At lag three, bidirectional causality was discovered between foreign reserves and foreign direct investment. Evidence of unidirectional causality running from exchange rate to foreign direct investment in lags one and three, was revealed. No causality existed between the duos at lag two. Based on the findings it is recommended that the policy makers establish the optimum exchange rate level that positively promotes foreign reserves and foreign direct investment. Keywords: Foreign Reserves, Exchange Rate, Foreign Direct Investment. JEL Classifications: C0; C32; F0